2009
DOI: 10.1007/s11162-009-9142-y
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of University–Industry Relationships and Academic Research On Scientific Performance: Synergy or Substitution?

Abstract: This paper evaluates whether university-industry relationships (UIR) and academic research activities have complementary effects on the scientific production of university lecturers. The analysis is based on a case study of two Spanish universities. We find that the effects of R&D contracts with industry, and academic research activity on scientific production are synergistic, but only when the R&D contracts account for a low percentage of a lecturer's total funding. This suggests that the positive effect of U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(23 citation statements)
references
References 44 publications
3
20
0
Order By: Relevance
“…They implicitly assume that contact with industry gives rise to a change in research orientation, resulting in a decrease in scientific output and an increase in commercial output. Other research mostly assessed quantitatively whether research outcome is directly affected by research sponsorship (Blumenthal et al 1997;Manjarrés-Henríquez et al 2009;Banal-Estanol, Jofre-Bonet, and Meissner 2010;Hottenrott and Thorwarth 2011;Lawson 2012) and the results suggest that industry funding may negatively affect scientific performance in terms of publications, but may also inspire patent productivity.…”
Section: Research Grants Sources Of Ideas and Research Outputmentioning
confidence: 99%
See 2 more Smart Citations
“…They implicitly assume that contact with industry gives rise to a change in research orientation, resulting in a decrease in scientific output and an increase in commercial output. Other research mostly assessed quantitatively whether research outcome is directly affected by research sponsorship (Blumenthal et al 1997;Manjarrés-Henríquez et al 2009;Banal-Estanol, Jofre-Bonet, and Meissner 2010;Hottenrott and Thorwarth 2011;Lawson 2012) and the results suggest that industry funding may negatively affect scientific performance in terms of publications, but may also inspire patent productivity.…”
Section: Research Grants Sources Of Ideas and Research Outputmentioning
confidence: 99%
“…In the following analysis, we test if -controlling for unobserved heterogeneity between professors -different sources of ideas translate into differences in research performance in subsequent years, a phenomenon that has been attributed directly to funding in the previous literature (Blumenthal et al 1997;Geuna 1997;Manjarrés-Henríquez et al 2009;Banal-Estanol, Jofre-Bonet, and Meissner 2010;Hottenrott and Thorwarth 2011). This previous work, however, did not allow concluding whether this effect was due to time constraints of researchers involved in industry funded projects, non-disclosure clauses, or due to an impact on the research content that leads to research agendas that are more aligned with industry interests rather than with scientific relevance.…”
Section: Econometric Set-upmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies have noted that positive effects only occur under specific conditions (Bonaccorsi et al 2006;Manjarrés-Henríquez et al 2009;Banal-Estañol et al 2013), whereas others have found that collaboration can have negative effects on scientific productivity (Bonaccorsi & Piccaluga 1994;Hottenrott & Thorwarth 2011;Blumenthal et al 1996;Manjarrés-Henríquez et al 2009;Banal-Estañol et al 2015).…”
Section: University-industry Collaboration and Scientific Productivitmentioning
confidence: 99%
“…Although several scholars have expressed concern regarding the potentially adverse effect of the growth of industrial funding upon the autonomy of university researchers and the quality of scientific production (Dasgupta and David, 1994), there is a growing body of evidence indicating that university researchers funded by industry are more productive than colleagues who are not in receipt of such funding (Gulbrandsen and Smeby, 2005). These studies suggest that industrial funding provides university researchers not only with additional financial resources but also relevant knowledge, generating synergistic effects on their scientific productivity, resulting in improved organisational performance (Manjarrés-Henríquez et al, 2009). …”
Section: Introductionmentioning
confidence: 99%